The Gold Coast. 1624 - 1638. - Gold Coast (Gold Coast, 1624)
The Dutch Commanders- & Captains-General on the Sold Coast under the Netherlands West-Indian Company. 1623---1639.
Furley Collection
Keywords: Gold Coast